2022
DOI: 10.1126/sciadv.abn3326
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity induces glucosylceramide that is secreted via exosomes for lysosomal degradation in glia

Abstract: Recessive variants in GBA1 cause Gaucher disease, a prevalent form of lysosome storage disease. GBA1 encodes a lysosomal enzyme that hydrolyzes glucosylceramide (GlcCer) into glucose and ceramide. Its loss causes lysosomal dysfunction and increased levels of GlcCer. We generated a null allele of the Drosophila ortholog Gba1b by inserting the Gal4 using CRISPR-Cas9. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 89 publications
0
32
0
Order By: Relevance
“…We previously showed that loss of fly homolog of PLA2G6 leads to an elevation of ceramides including GlcCer ( Lin et al, 2018 ). GlcCer accumulation is also observed in flies that lack the fly homolog of GBA1 ( Wang et al, 2022a ), the gene that causes Gaucher disease ( Sidransky, 2004 ; Wong et al, 2004 ). We performed immunostaining in the cerebellum and midbrain of the Pla2g6 KO/G373R and homozygous Pla2g6 G373R/G373R animals.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that loss of fly homolog of PLA2G6 leads to an elevation of ceramides including GlcCer ( Lin et al, 2018 ). GlcCer accumulation is also observed in flies that lack the fly homolog of GBA1 ( Wang et al, 2022a ), the gene that causes Gaucher disease ( Sidransky, 2004 ; Wong et al, 2004 ). We performed immunostaining in the cerebellum and midbrain of the Pla2g6 KO/G373R and homozygous Pla2g6 G373R/G373R animals.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that loss of fly homolog of PLA2G6 leads to an elevation of ceramides including glucosylceramides (GlcCer) (Lin et al, 2018). GlcCer accumulation is also observed in flies that lack the fly homolog of GBA1 (Wang et al, 2022a), the gene that causes Gaucher disease (Sidransky, 2004; Wong et al, 2004). We performed immunostaining in the cerebellum and midbrain of the PLA2G6 KO/G373R and homozygous PLA2G6 G373R/G373R animals.…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been demonstrated that Gba1b is expressed predominantly within glia, rather than neurons, in the fly brain (Wang et al, 2022). Using the same CRIMIC Gba1b line, in which Gba1b gene expression is disrupted, we co-expressed UAS-mCherry.nls under the Gba1b endogenous promoter (Lee et al, 2018).…”
Section: Resultsmentioning
confidence: 99%